(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background of the study: Caution with regard to dietary intake during pregnancy has been advised since ancient times and this is true even today, more so for the use of drugs in pregnancy. Drug use during early pregnancy is not different from non-pregnant women. The knowledge of women regarding teratogenic drugs has an effect on their health.Methodology: Quantitative approach with a typical descriptive design was adopted in the present study. Purposive sampling technique was used for the selection of the sample. A close-ended structured knowledge questionnaire was used to assess the knowledge of women on teratogenic drugs. The study was conducted in selected Hospital, at Mangalore, with the sample size of 100 women. After data collection, the information booklets regarding teratogenic drugs were distributed to women to improve their knowledge.Results: Descriptive and inferential statistics were used to analyse the data. Assessment of the level of knowledge of the women showed that the highest percentage (64%) of the sample had moderate knowledge; 25% of the women had poor knowledge, 9% of the women had good knowledge and only two percent of the women had very good knowledge on teratogenic drugs. Present study results reveals that there was significant association between knowledge score and demographic variable.Conclusion: The overall knowledge regarding teratogenic drugs in the study population was 45.67%. Hence, it is concluded that the knowledge of women was not adequate enough therefore further improvement in knowledge was still needed in this area.